ANALYTICAL TRUSS MODELS OF FRP SHEAR STRENGTHENED REINFORCED CONCRETE BEAMS WITHOUT STIRRUPS - YIN, HOR (2014)
Strengthening of reinforced concrete (RC) and other structures using fibre reinforced polymer (FRP) composites has become very popular in the last two decades. This has been due to both the needs for maintaining and upgrading essential infrastructure in all parts of the world, and the well-known advantages of FRP composites including both good corrosion resistance and ease for site handling due to their light weight. The continuous reduction in the material cost of FRP composites has also contributed to their popularity.